2015
DOI: 10.32607/20758251-2015-7-4-128-135
|View full text |Cite
|
Sign up to set email alerts
|

Sulfoxides, Analogues of L-Methionine and L-Cysteine As Pro-Drugs against Gram-Positive and Gram-Negative Bacteria

Abstract: The problem of resistance to antibiotics requires the development of new classes of broad-spectrum antimicrobial drugs. The concept of pro-drugs allows researchers to look for new approaches to obtain effective drugs with improved pharmacokinetic and pharmacodynamic properties. Thiosulfinates, formed enzymatically from amino acid sulfoxides upon crushing cells of genus Allium plants, are known as antimicrobial compounds. The instability and high reactivity of thiosulfinates complicate their use as individual a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…The Cys115/His mutant form was prepared as follows: the mgl‐sp‐Blue plasmid was obtained by cloning the megL_sporog gene into the Bluescript II vector SK(±); the mutagenesis was performed by PCR. The fragment containing T/C (343) and G/A (344) substitutions was amplified using mgl‐sp‐Blue as the template by PCR with the primers F1, F2, R1, and R2: lefttrue(F1true) GGAGATATACCATGGAGAATATTlefttrue(F2true) CTTTATATGGGtrueboldCAC¯ACATTTGCAlefttrue(R1true) TGCAAATGTtrueboldGTG¯CCCATATAAAGlefttrue(R2true) TGGTTTTAATGCATTCTTTACCTCA …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Cys115/His mutant form was prepared as follows: the mgl‐sp‐Blue plasmid was obtained by cloning the megL_sporog gene into the Bluescript II vector SK(±); the mutagenesis was performed by PCR. The fragment containing T/C (343) and G/A (344) substitutions was amplified using mgl‐sp‐Blue as the template by PCR with the primers F1, F2, R1, and R2: lefttrue(F1true) GGAGATATACCATGGAGAATATTlefttrue(F2true) CTTTATATGGGtrueboldCAC¯ACATTTGCAlefttrue(R1true) TGCAAATGTtrueboldGTG¯CCCATATAAAGlefttrue(R2true) TGGTTTTAATGCATTCTTTACCTCA …”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have showed that PLP‐dependent MGL (EC 4.4.1.11) from Citrobacter freundii catalyzes the β‐elimination reaction of alliin and other S‐substituted l ‐cysteine sulfoxides to form allicin or S‐alkylthiosulfinates:
…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The band at 500 nm is typical of quinonoid intermediates that occur in reactions catalyzed by PLP‐dependent enzymes . The absorption spectrum of MGLs from C. sporogenes and C. tetani contains a band with a maximum at 505 nm , while this band is barely noticeable in the spectrum of MGL from C. freundii . The spectrum was resolved into bands corresponding to individual electron transitions.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we provided evidence for the cytotoxicity of MGL from C. sporogenes, C. tetani, and Citrobacter freundii MGL using K562, PC-3, LnCap, MCF7, SKOV-3, and L5178y tumor cell lines (9). We also reported the capability of MGL to catalyze the formation of the potent antibacterial agent allicin or Salkylthiosulfinates from substrate analogues, such as alliin and S-substituted L-cysteine sulfoxides (10,11).…”
Section: Introductionmentioning
confidence: 94%